Migration experiences, life conditions, and drug use practices of Russian-speaking drug users who live in Paris: a mixed-method analysis from the ANRS-Coquelicot study - Yaël Tibi-Lévy; Daria Serebryakova; Marie Jauffret-Roustide; ANRS-Coquelicot Study Group (Harm Reduction Journal, 2020)
Abstract Background After the collapse of the Soviet Union at the beginning of the 1990s, people who inject drugs spiked in Eastern Europe. Facing local repression and an array of factors encouraging emigration, some users have migrated to France. This population now make up to a third of the patient list of some harm reduction services in Paris. This article aims to present original data on the sociodemographic profiles of these users, on their migration trajectory, their life conditions, and on the evolution of their drug use practices since arriving in Paris. Methods Data were collected as part of the ANRS-Coquelicot Survey, an HIV and HCV seroprevalence study among French-speaking people who use drugs. A sub-sample of Russian-speaking drug users who had relocated from Eastern Europe to live in Paris completed a quantitative questionnaire (N = 150) and a qualitative semi-structured interview (N = 20). The survey aimed to describe participants’ backgrounds, and a thematic analysis of interviews was conducted to explore participants’ migration histories, their life conditions in Paris, and their drug use practices before and after arriving in France. Results This study highlights the great vulnerability of the participating population, often following a loss of social status after migrating to France. Another important finding is that participants had better access to harm reduction tools and reduced their risk of exposure to HIV and HCV infections linked to needle sharing. Although 60% said they had already shared a syringe in their lifetime (49.9% of them in their home country), the proportions shrank to 13.9% after they arrived in France and to 9.3% in the month before the study, a proportion that is lower than among French-speaking people who use drugs. Conclusions Our main findings on the profiles and behaviors of the study population lead us to make two recommendations: to offer stronger global care to these users in Paris and to reform drug policy in their home countries by integrating it into a public health approach.